2021
DOI: 10.1186/s12955-020-01635-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing health behavior practice in patients with coronary artery diseases

Abstract: Background The purpose of this study was to investigate the relationships among cardiac rehabilitation knowledge, educational need and health behavior practice in patients with coronary artery disease and explain factors influencing health behavior practice. Method The research participants were 189 patients with coronary artery disease from general hospital located in Korea. Self-evaluation questionnaires were used to collect the data. Data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Another systematic review also reported that smoking cessation can reduce the risk of death and myocardial infarction in CAD patients by 30%. 18 Healthy lifestyle behavior can reduce the risk of CAD severity, which has been proven through various studies. Risk reduction through behavior in CAD patients is essential in mediating health conditions after coronary angioplasty.…”
Section: Marlina Marlina Et Al: Relationship Between Self-management ...mentioning
confidence: 97%
“…Another systematic review also reported that smoking cessation can reduce the risk of death and myocardial infarction in CAD patients by 30%. 18 Healthy lifestyle behavior can reduce the risk of CAD severity, which has been proven through various studies. Risk reduction through behavior in CAD patients is essential in mediating health conditions after coronary angioplasty.…”
Section: Marlina Marlina Et Al: Relationship Between Self-management ...mentioning
confidence: 97%
“…(χ 2 18.52, p<0.001), (χ 2 20.13, p<0.013) respectively, this may be due to the influence of family members, support groups, or the doctors and nurses inspire patients to modify poor lifestyle behaviour since the initial diagnosis. The other variables were not assessed in this study 16 .…”
Section: Correlation Between Perceived Health Behaviours and Learning...mentioning
confidence: 99%
“…6 It is suggested that individuals with CAD constantly practice healthy habits to avoid recurrence and deterioration during acute treatment. 10 Knowledge about health, in particular, may alter a person's conception of what motivates them to engage in certain behaviors connected to their health and their attitude toward engaging in such actions, thereby boosting the level of engagement. 11 Despite the significance of self-care, patients rarely, if ever, obtain comprehensive health information from their medical professionals.…”
Section: Introductionmentioning
confidence: 99%